2004
DOI: 10.1111/j.1365-2621.2004.tb15512.x
|View full text |Cite
|
Sign up to set email alerts
|

Ohmic Cooking of Processed Meats and its Effects on Product Quality

Abstract: es es es es, and a 20-min holding time had little , and a 20-min holding time had little , and a 20-min holding time had little , and a 20-min holding time had little , and a 20-min holding time had little influence on the quality of ohmic sausages. In addition, ohmic sausages were always found to be similar to influence on the quality of ohmic sausages. In addition, ohmic sausages were always found to be similar to influence on the quality of ohmic sausages. In addition, ohmic sausages were always found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 13 publications
5
57
2
Order By: Relevance
“…This was largely due to impact of amount of heat generated during ohmic heating, which was directly related to current induced by the voltage gradient in the applied electric field as reported earlier by different researchers [3,16,26]. Further, our findings are also in commensuration with several researchers that higher voltage gradients cause a decrease in ohmic heating time of the product [9,17,27,32].…”
Section: Heating Rate During Ohmic Heatingsupporting
confidence: 77%
“…This was largely due to impact of amount of heat generated during ohmic heating, which was directly related to current induced by the voltage gradient in the applied electric field as reported earlier by different researchers [3,16,26]. Further, our findings are also in commensuration with several researchers that higher voltage gradients cause a decrease in ohmic heating time of the product [9,17,27,32].…”
Section: Heating Rate During Ohmic Heatingsupporting
confidence: 77%
“…By comparison, ohmic heating, which is suggested to heat food more rapidly and uniformly leading to a milder thermal treatment (Icier and Bozkurt 2009), can provide even greater energy efficiencies as the electrical energy is directly channelled through the product, although its commercial application in the meat sector has not yet been adopted. Previous work on ohmic heating of meat products has been limited to comminuted material (Shirsat et al 2004;Piette et al 2004) with both studies yielding promising results in terms of product quality (i.e. similar or improved texture and colour attributes).…”
Section: Introductionmentioning
confidence: 96%
“…Although they mentioned that the quality of the ohmic cooked product was acceptable, they reported several problems arise to develop industrial ohmic cooking systems for meat products. These problems were mainly described by the difficulty arisen in providing the good contact between the samples and the electrode surfaces (de Alwis and Fryer, 1992), and the electrical conductivity differences within the heterogeneous meat structure during treatment (Piette et al, 2004). Ozkan et al (2004) suggested the usage of flat meat patties and plate heating to assure a good contact between the sample and electrode surface.…”
Section: Introductionmentioning
confidence: 99%